2022
DOI: 10.1155/2022/7261486
|View full text |Cite
|
Sign up to set email alerts
|

Solasonine Induces Apoptosis and Inhibits Proliferation of Bladder Cancer Cells by Suppressing NRP1 Expression

Abstract: Solasonine, a steroidal alkaloid extracted from Solanum nigrum L., has been found to exert inhibitory effect on cancers. However, the underlying anticancer mechanisms of solasonine, particularly in urinary bladder cancer (BC), remain unclear. In this study, we identified the potential targets and biological functions associated with solasonine activity using a bioinformatics approach. Ingenuity pathway analysis revealed that neuropilin-1 (NRP1) and other signaling pathways, such as PI3K/AKT and ERK/MAPK pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
9
0
Order By: Relevance
“…12,15,17,26,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][51][52][53][54] Similar findings were reported for other tumor types, describing TGF-β and other signaling pathways as potential targets of NRP regulation. [76][77][78][79] Additionally, invasion, migration and metastasis were also found to be strongly modulated by both NRPs in different solid tumor models, 24,80,81 supporting roles for NRP1 and NRP2 in mechanisms underlying tumor progression and spread. Nevertheless, while these findings highlight interesting function for NRPs in HCC tumor progression and invasion abilities, further studies are needed to identify the exact mechanisms and signaling pathways modulated by NRP1 and NRP2.…”
Section: Discussionmentioning
confidence: 82%
“…12,15,17,26,[35][36][37][38][39][40][41][42][43][44][45][46][47][48][51][52][53][54] Similar findings were reported for other tumor types, describing TGF-β and other signaling pathways as potential targets of NRP regulation. [76][77][78][79] Additionally, invasion, migration and metastasis were also found to be strongly modulated by both NRPs in different solid tumor models, 24,80,81 supporting roles for NRP1 and NRP2 in mechanisms underlying tumor progression and spread. Nevertheless, while these findings highlight interesting function for NRPs in HCC tumor progression and invasion abilities, further studies are needed to identify the exact mechanisms and signaling pathways modulated by NRP1 and NRP2.…”
Section: Discussionmentioning
confidence: 82%
“…49,50 These pathways are often overactivated in BC, and targeted therapies to inhibit their activation have been proposed. 51 Notably, TEC has been shown to ameliorate proliferation and inflammation in TNF-α-stimulated HFLS-RA cells by repressing the TLR4/NLRP3/NF-κB signaling pathway. 52 Previous studies have also indicated that RAB27B overexpression facilitates the activation of the PI3K/AKT/mTORC1 pathway and the ERK/MAPK pathway in HEK293 cells.…”
Section: Discussionmentioning
confidence: 99%
“…TMPRSS2, a key gene mediating the entry of SARS-CoV-2 into humans, is highly expressed in prostate cancer and its high expression could promote the development of prostate cancer (37)(38)(39)(40). NRP1, serving as a key factor of SARS-CoV-2 virus infection (41), could increase the susceptibility of cancer patients to SARS-CoV-2 virus and targeting (42), and its overexpression is associated with poor prognosis in bladder cancer cells and hepatocellular carcinoma, and inhibiting its expression could promote tumor cell apoptosis (43,44). In addition, the increased expression of SCARB1 could promote cell transformation towards malignancy of clear cell renal cell carcinoma leading to poor prognosis of patients (45), while the over-expression of AXL could accelerate EGFR mutation and promote the metastasis, invasion or drug resistance of tumors such as lung cancer (46), colorectal cancer (47), pancreatic cancer (48) and prostate tumor (49).…”
Section: Discussionmentioning
confidence: 99%